PENINGKATAN HASIL BELAJAR SISWA DENGAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPS KELAS IV SDN 101777 SAENTIS - Fira Astika Wanhar; Meliyani Meliyani (JURNAL TEMATIK, 2020)
This study aims to determine the increase instudent learning outcomes using the Problem Based Learning model in social studies learning material on social problems in the local environment grade 4th SDN 101777 Saentis. This type of research is a classroom action research (PTK) which is conducted in two cycles. The instrument used in this study is based on the results of observations in each cycle. Subjects in the study were 30 fourth grade students of SDN 101777 Saentis. The preliminary data of the study used a pretest value which showed an average value of 64.50. Whereas the student learning outcomes also increased, where from the average obtained from the post test cycle I was 70.83 and had student learning completeness of 53.33% (16 students) and increased in the results of the post test cycle II, namely obtaining a value an average of 88.16 and had student learning completeness of 93.33% (28 students). This proves that the next cycle is not necessary. Therefore, the application of the Problem Based Learning learning model has been proven to increase the activity and social studies learning outcomes of students on social issues in the local environment in grade 4th SDN 101777 Saentis